PENGGUNAAN KALKULATOR OBAT DALAM MENGURANGI MEDICATION ERROR PADA ANAK DI EMERGENCY CARE: KAJIAN LITERATUR [THE USE OF A DRUG DOSAGE CALCULATOR IN REDUCING MEDICATION ERROR IN CHILDREN IN EMERGENCY CARE: A SYSTEMATIC LITERATURE STUDY] - Elfrida Silalahi; La Ode Abd Rahman (Nursing Current: Jurnal Keperawatan, 2022)
Children are at high risk of medication errors. Emergency room is one of the rooms that are prone to medication errors. The most common causes are medication dosage errors, inaccurate child weight, duplicate doses, wrong medications, and delayed or missed doses. Some applications have been widely used to reduce medication errors in paediatric emergency care. This literature review aims to determine the use of drug dose calculators in reducing medication errors in children in emergency care. The search for articles in this study uses seven databases including EBSCO, ScienceDirect, Scopus, Wiley, ProQuest, PubMed and Google Scholar. The inclusion criteria are articles in full text, written in Indonesian or English, and published within the last five years from 2017-2021. Exclusion criteria include literature review articles and procedural studies. This study uses a simplified approach by Aveyard in 2010 and uses critical appraisal developed by Woolliams in 2009 to assess each article. The search results show that there are six articles mentioning a drug calculator can be a scientific drug calculator application for emergency care. However, there is also a drug calculator that does not stand alone as an application but as part of another application which is a guideline for handling children in emergency care. BAHASA INDONESIA ABSTRAK Anak merupakan populasi yang rentan mengalami kejadian kesalahan pengobatan. Salah satu lingkungan yang rawan terjadinya kesalahan pengobatan pada anak adalah ruang rawat darurat. Penyebab paling sering adalah kesalahan penghitungan dosis obat, berat badan anak yang tidak akurat, dosis duplikat, obat yang salah, dan dosis yang tertunda atau terlewatkan. Penggunaan aplikasi telah banyak digunakan untuk mengurangi kesalahan pengobatan di emergency care anak. Kajian literatur ini bertujuan untuk mengetahui penggunaan kalkulator obat dalam mengurangi kesalahan pengobatan pada anak di emergency care. Penelusuran studi dalam artikel ini menggunakan tujuh database diantaranya EBSCO, ScienceDirect, Scopus, Wiley, ProQuest, PubMed dan Google Scholar. Kriteria inklusi yakni artikel dalam bentuk full text, berbahasa Indonesia atau bahasa Inggris, serta tahun penerbitan lima tahun terakhir dari tahun 2017-2021. Kriteria eksklusi antara lain artikel kajian literatur, dan studi prosedural. Penelitian ini menggunakan metode simplified approach Aveyard (2010) serta menggunakan critical appraisal yang dikembangkan oleh Woolliams (2009) untuk menilai tiap artikel. Pada penelusuran ditemukan enam artikel dengan hasil bahwa kalkulator obat dapat berupa aplikasi kalkulator obat ilmiah khusus emergency care. Namun ada juga kalkulator obat yang tidak berdiri sendiri sebagai aplikasi tetapi merupakan bagian dari aplikasi lain yang merupakan pedoman penanganan anak di emergency care.